circEPSTI1 Acts as a ceRNA to Regulate the Progression of Osteosarcoma - Tan, Xinyu; Tan, Duxun; Li, Haomiao; Lin, Ye; Wen, Zhishen; Zeng, Canjun (Current Cancer Drug Targets, 2020)
Background: Recent studies have reported the vital roles of circular RNAs (circRNAs) in tumor progression. However, the function and expression profile of most circRNAs in osteosarcoma remain unclear. Methods: We examined the expression of circEPSTI1, a circRNA, in 50 paired adjacent normal tissues and osteosarcoma tissues by qRT-PCR. Then, we further explored the function of circEPSTI1 in osteosarcoma progression in vitro and in vivo. For example, cell proliferation and migration were examined. Some experiments were performed to explore the regulatory function of circEPSTI1 in miRNA and to investigate the potential role of circEPSTI1 in osteosarcoma. Results: We found that circEPSTI1 was significantly upregulated in osteosarcoma. Inhibition of circEPSTI1 suppressed the osteosarcoma cancer cell proliferation and migration in vitro. Dual luciferase reporter assay showed that circEPSTI1 and MCL1 (myeloid cell leukaemia 1) could bind to miR-892b and that MCL1 and circEPSTI1 were targets of miR-892b. Conclusion: Thus, the circEPSTI1-miR-892b-MCL1 axis affected osteosarcoma progression through the miRNA sponging mechanism. circEPSTI1 may serve as a target and biomarker for osteosarcoma treatment.
Keywords: MCL1